SWEAR WORD TYPOLOGY AND FUNCTIONS IN SASAK TEENAGERS’ SPEECH IN MEKARSARI SUB-VILLAGE OF SUMBAWA - Yayuk Hasanah; Iwan Jazadi (GLOBAL: Education Language and Humanity Journal, 2025)
This study investigates the types and functions of swear words used by Sasak teenagers in Mekarsari Sub-Village, Sumbawa Regency. The research is guided by two main questions: (1) What types of swear words are used by Sasak teenagers? (2) What are the functions of these swear words in their daily interactions? A qualitative research design was employed, involving ten male teenagers as participants. Data were collected through observation, semi-structured interviews, and documentation, and analyzed using Miles and Huberman’s interactive model (data reduction, data display, and conclusion drawing). The findings reveal that Sasak teenagers frequently use various swear words, which can be categorized into five main types: swear words related to sex, excretion, body parts, devils, and animals. Among these, swear words from sex, devils, and animals were most dominant. Furthermore, the use of these expressions served four main pragmatic functions: expression, exploration, persuasion, and entertainment. The results indicate that swearing has become a habitual linguistic practice embedded in the teenagers' social interactions and emotional expressions. This study highlights the importance of understanding local linguistic behavior to inform language education, youth character development, and sociolinguistic awareness in multicultural settings.